Cognitive, linguistic, and motor stimulation in individuals with an early-stage Alzheimer's diagnosis: A new concept of early stimulation (Research, Society and Development, 2025)
Alzheimer's disease is a neurodegenerative condition that progressively affects cognitive, linguistic, and motor functions, impacting patients' quality of life. This article analyzes the importance of early stimulation in individuals diagnosed in the initial stages, highlighting interventions in these areas. Through a theoretical and documentary review, strategies are proposed to promote autonomy, reduce stress, and improve well-being. The role of caregivers and family members is emphasized, as they require training and support for proper implementation. Additionally, the legal framework supporting patients’ rights is examined. This research serves as a foundation for future studies, redefining early stimulation as an innovative strategy to slow cognitive decline and improve quality of life.